Lupus anticoagulant identifies two distinct groups of patients with different antibody patterns. Issue 172 (December 2018) - Pengo, V.; Del Ross, T.; Ruffatti, A.; Bison, E.; Cattini, M.G.; Pontara, E.; Testa, S.; Legnani, C.; Pozzi, N.; Peterle, D.; Acquasaliente, L.; De Filippis, V.; et al.
Abstract: Background: Whether antibodies directed to β2-Glycoprotein I (aβ2GPI) are responsible for LA activity is not well defined. However, in the absence of such antibodies the molecule responsible for LA phenomenon is unknown. Objective: The aim of this study was the biochemical identification of the target antigen epitope of aPL responsible of LA activity in the absence of aβ2GPI antibodies together with the biological and clinical characteristics of these patients in comparison with classical triple positive patients. Patients/methods: A comparison of patients with LA without (LA+/aβ2GPI−) and those with (LA+/aβ2GPI+) associated aβ2GPI antibodies was performed. Size exclusion chromatography and analytical chromatography were used to identify the molecule with LA activity in patients LA+/aβ2GPI-. Results and conclusions: Analytical size-exclusion chromatography revealed a peak of 996Kd with LA activity perfectly overlapping that of IgM anti phosphatidylserine/prothrombin (aPS/PT) antibodies. Similarly, all the 25 LA+/aβ2GPI− patients were positive for aPS/PT antibodies. LA+/aβ2GPI− compared to 33 LA+/aβ2GPI+ patients turned out to be significantly older, with a lower rate of previous thromboembolic events and a weaker LA activity. Search for aPS/PT and aβ2GPI antibodies in patients with LA is useful to identify two subgroups of LA at different risk of thromboembolic events. Highlights: Isolated LA (LA+, aβ2GPI-) shows a peculiar pattern of antiphospholipid antibodies (aPS/PT usually of IgM isotype). Isolated LA are older, at lower thrombotic risk, and have a weaker LA potency with respect to LA+/aβ2GPI+. The distinction is useful in clinical practice when deciding the appropriate treatment.